ETHNOSCIENCE ANALYSIS OF RUMAH GADANG CONSTRUCTION BASED ON MINANGKABAU NATURAL LOCAL WISDOM - Nurul Annisa (Pendidikan IPA, FMIPA, UNP, 2022)
The construction of the Minangkabau traditional home is distinctive. The gadang house was built with local wisdom, which can be related to the Minangkabau traditional community's understanding of how to interact with nature. This essay examines the components and modifications of Rumah Gadang's construction culture system from the perspectives of ethnoscience and community wisdom. The Gadang House, which serves as the King's Palace, is the subject of the research, and the methodology utilized is descriptive qualitative with direct surveys to the field utilizing interview techniques. The results of the study show that the construction and spatial arrangements in the Rumah Gadang building are very closely related to the local wisdom of the Minangkabau people and also the application of science elements in its construction.